2020
DOI: 10.1177/0284185120932386
|View full text |Cite
|
Sign up to set email alerts
|

Increased tortuosity of bilateral distal internal carotid artery is associated with white matter hyperintensities

Abstract: Background Although the pathophysiology of white matter hyperintensities remains unclear, we can recently explore the possible relationship with white matter hyperintensities by using quantitative parameter. Purpose To demonstrate the relationship between bilateral distal internal carotid arterial tortuosity and total brain white matter hyperintensities volume in elderly individuals. Material and Methods A total of 345 patients (age > 65 years) with brain magnetic resonance (MR) examinations were retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 49 publications
1
8
1
1
Order By: Relevance
“…Thus, based on the CFD TAMV and the WSS levels, both these participants were at increased risk for stroke as previously described [7; 36; 47]. While Liu et al found that large vessel vasculopathy was associated with increased white matter disease in adults with SCD [48], our study demonstrates that cerebrovascular events occur in children with SCD with even mild large vessel vasculopathy, suggesting additional pathophysiologic mechanisms which contribute to cerebrovascular events. Certainly, large vessel vasculopathy contributes to the development of silent infarcts as well as overt cerebrovascular disease, as Guilliams et al found a greater distribution and overall density of silent cerebral infarcts in areas with large vessel vasculopathy [49].…”
Section: Discussionsupporting
confidence: 79%
“…Thus, based on the CFD TAMV and the WSS levels, both these participants were at increased risk for stroke as previously described [7; 36; 47]. While Liu et al found that large vessel vasculopathy was associated with increased white matter disease in adults with SCD [48], our study demonstrates that cerebrovascular events occur in children with SCD with even mild large vessel vasculopathy, suggesting additional pathophysiologic mechanisms which contribute to cerebrovascular events. Certainly, large vessel vasculopathy contributes to the development of silent infarcts as well as overt cerebrovascular disease, as Guilliams et al found a greater distribution and overall density of silent cerebral infarcts in areas with large vessel vasculopathy [49].…”
Section: Discussionsupporting
confidence: 79%
“…The prevalence of carotid artery kinking was significantly higher in WMHs patients, and kinking may be a risk factor of WMHs [ 18 , 43 ]. Moreover, recent studies established an association between WMHs and arterial tortuosity which was evaluated using the tortuosity index [ 17 , 44 ]. However, these studies excluded the patients with stroke and only concerned internal carotid arteries tortuosity.…”
Section: Discussionmentioning
confidence: 99%
“…Arterial tortuosity causes WMHs through various possible mechanisms. First, increased arterial tortuosity promotes hemodynamic variation in cerebral blood flow which can result in hypoperfusion and chronic brain ischemia and then may increase the risk of developing WMHs [ 17 , 43 ]. Second, the microembolism may be another mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First of all, the presence of complex aortic arch anatomy may cause an increased risk of neurological complications [2][3][4]. Difficulty of cannulation that can be attributed to technical problems related with anatomical factors is associated with subclinical ischemic events.…”
Section: To the Editormentioning
confidence: 99%